2021
DOI: 10.4103/lungindia.lungindia_794_20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proning in patients with COVID-19 acute hypoxemic respiratory failure receiving noninvasive oxygen therapy

Abstract: Background: Novel coronavirus (SARS-CoV-2) infection is associated with hypoxemic respiratory failure. Mechanical ventilation (MV) is reported to have high mortality in SARS-CoV-2 acute respiratory distress syndrome. We aimed to investigate whether awake prone positioning (PP) can improve oxygenation and prevent intubation when employed early. Methods: This prospective interventional study included proven coronavirus disease 2019 (COVID-19) patients with room air satura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A study carried out in England by Winearls et al 29 reported that the use of PP with CPAP significantly improved the ROX index in patients with COVID‐19. Similarly, Sryma et al 30 found significant improvement in the ROX index values in the study group compared with that in the control group 30 min after PP initiation.…”
Section: Discussionmentioning
confidence: 62%
“…A study carried out in England by Winearls et al 29 reported that the use of PP with CPAP significantly improved the ROX index in patients with COVID‐19. Similarly, Sryma et al 30 found significant improvement in the ROX index values in the study group compared with that in the control group 30 min after PP initiation.…”
Section: Discussionmentioning
confidence: 62%
“… 30 In addition, only a few studies have utilized control group for the evaluation of awake PP. 13 , 18 , 19 In all these studies, the assessment for improved oxygenation was undertaken as early as 1 hour 13 , 18 till the end of day one. 19 These studies’ results highlighting the improvement in oxygenation following such a short duration of awake PP could possibly be implicated to the transient lung recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies (12 observational, 9 retrospective [15][16][17][18][19][20][21][22][23] and 3 prospective [24][25][26], and 5 RCTs [27][28][29][30][31]) met our inclusion criteria (Table 1). Six studies were done in the ICU and 11 outside the ICU (Table 1).…”
Section: Prone Position In Nonintubated Patientsmentioning
confidence: 99%